2013
DOI: 10.5433/1679-0359.2013v34n4p1935
|View full text |Cite
|
Sign up to set email alerts
|

Produção e composição química-bromatológica de Tifton 85 (Cynodon dactylon L. Pers) sob pastejo contínuo no período hibernal

Abstract: ResumoO objetivo do presente trabalho foi avaliar o comportamento produtivo e qualitativo dos constituintes estruturais da pastagem de Tifton 85, no período de maio a setembro de 2010, submetido ao pastejo. O experimento foi realizado no município de Luiziana, região Noroeste do estado do Paraná. Avaliouse a produção total de massa de forragem, de lâminas foliares, colmos e material morto e a relação folha:colmo. A composição química-bromatológica foi determinada por meio das análises de fibra em detergente ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
3
6
0
1
Order By: Relevance
“…NERES et al, 2012;MARCHESAN et al, 2013). Many studies have reported that CP content increased with progressive increases of N application, and this study demonstrated a linear relationship between them in the 2nd, 3rd, and 4th cuts (Figure 14).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…NERES et al, 2012;MARCHESAN et al, 2013). Many studies have reported that CP content increased with progressive increases of N application, and this study demonstrated a linear relationship between them in the 2nd, 3rd, and 4th cuts (Figure 14).…”
Section: Resultssupporting
confidence: 61%
“…A LSR of approximately 1.2 contains about two thirds of total DM is available in leafs. As tillers age, LSR decreases owing to stem elongation; the stem has a higher fiber content and less protein (CUTRIM JUNIOR et al, 2014;MARCHESAN et al, 2013). However, LSR also varies with the season (MOREIRA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Marchesan et al (2013), assessing the production and chemical composition of Tifton 85 under continuous grazing during the winter, observed mean CP levels of 14.34%, similar to that obtained during the winter in the present study.…”
Section: Forage Production and Qualitysupporting
confidence: 69%
“…Considering that most Brazilian milk production occurs on pastures, where feed is less expensive and management more economical, the provision of good-quality pastures can have a significant impact on a small rural property (Quaresma et al, 2011). Marchesan et al (2013) reported that for satisfactory animal behavior, feed with a nutritional value adequate to meet the needs of production animals must be offered, thus optimizing the production system and obtaining satisfactory growth rates.…”
Section: Correlation Of Forage Production and Quality With Milk Produmentioning
confidence: 99%
“…The Cynodon genus stands out in dairy cattle production, since it has a high forage production potential, being able to surpass 25,000 kg -1 ha -1 year -1 of dry matter , with good nutritional value, with crude protein content values exceeding 11% of the dry matter (DE MATOS et al, 2013;MARCHESAN et al, 2013;SANCHES et al, 2015).…”
Section: Introductionmentioning
confidence: 99%